Apoptosis Induced by Tanshinone IIA and Cryptotanshinone Is Mediated by Distinct JAK/STAT3/5 and SHP1/2 Signaling in Chronic Myeloid Leukemia K562 Cells - Jung, Ji Hoon (Hindawi Publishing Corporation, 2013)
Though tanshinone IIA and cryptotanshinone possess a variety of biological effects such as anti-inflammatory, antioxidative, antimetabolic, and anticancer effects, the precise molecular targets or pathways responsible for anticancer activities of tanshinone IIA and cryptotanshinone in chronic myeloid leukemia (CML) still remain unclear. In the present study, we investigated the effect of tanshinone IIA and cryptotanshinone on the Janus activated kinase (JAK)/signal transducer and activator of transcription (STAT) signaling during apoptotic process. We found that both tanshinone IIA and cryptotanshinone induced apoptosis by activation of caspase-9/3 and Sub-G1 accumulation in K562 cells. However, they have the distinct JAK/STAT pathway, in which tanshinone IIA inhibits JAK2/STAT5 signaling, whereas cryptotanshinone targets the JAK2/STAT3. In addition, tanshinone IIA enhanced the expression of both SHP-1 and -2, while cryptotanshinone regulated the expression of only SHP-1. Both tanshinone IIA and cryptotanshinone attenuated the expression of bcl-x(L), survivin, and cyclin D1. Furthermore, tanshinone IIA augmented synergy with imatinib, a CML chemotherapeutic drug, better than cryptotanshinone in K562 cells. Overall, our findings suggest that the anticancer activity of tanshinone IIA and cryptotanshinone is mediated by the distinct the JAK/STAT3/5 and SHP1/2 signaling, and tanshinone IIA has the potential for combination therapy with imatinib in K562 CML cells.